How Students of The Yemeni University of Science and Technology Perceive The Quality of The University Services According to The Service Quality Measure (SERVQUAL) - Alghaili, Riyadh (The Arab Journal of Administration, 2018)
The aim of this study is to identify the level of awareness among university of science and technology students on the service quality that`s presented by the university – state study on the university of science and technology. The study is based on the gap theory with the use of the measurement model (SERVQUAL). The questionnaire has been used as the main tool to collect the data from the study population, and this questionnaire has two parts one of them is measuring the level of importance for that services from the students, point of view. The questionnaire has delivered with random sample method. The analytical descriptive method has been used to test the hypotheses of the study. The question emerged from the President to study the following questions: What level of awareness of the University of Science and Technology of the quality of services provided by the university students? How important is the quality of those services, according to its dimensions and arranged for the students? How much of the gap between the perceptions of students and their expectations for the level of quality of services provided at the University of Science and Technology? The study concluded that the level of quality of the services presented form the university is weak and not fulfilling the needs and expectation for the students, the study also found that there are significant statistically differences between the comprehension of students and their expectation of the quality of the service presented by university like student’s kindness, the quick response, dependence and security.